2020
DOI: 10.1038/s41398-020-00954-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in dementia with Lewy bodies: a human post-mortem study

Abstract: Dementia with Lewy bodies (DLB) is the second most common neurodegenerative cause of dementia, behind Alzheimer's disease (AD). It is now established that cerebral inflammation has a key role in the aetiology and progression of AD, but this has yet to be confirmed in DLB. We aimed to determine the neuroinflammatory profile in the cerebral cortex of a large cohort of DLB cases. Thirty post-mortem confirmed DLB cases and twenty-nine matched controls were immunolabelled (Brodmann area 21) and quantified for: neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 51 publications
3
39
2
2
Order By: Relevance
“…Control n = 12, PDND n = 16, PDD n = 10. Quantification of parenchymal CD4 + (p = 0.081) and CD8 + T lymphocytes (p = 0.434) per mm 2 Notably, we did not observe any significant differences in tau pathology between PDND and PDD cases. In agreement, semi-quantitative scoring in a large postmortem study revealed similar levels or neurofibrillary tau tangles in the temporal, mid-frontal, and parietal cortex of PDND and PDD cases [38].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Control n = 12, PDND n = 16, PDD n = 10. Quantification of parenchymal CD4 + (p = 0.081) and CD8 + T lymphocytes (p = 0.434) per mm 2 Notably, we did not observe any significant differences in tau pathology between PDND and PDD cases. In agreement, semi-quantitative scoring in a large postmortem study revealed similar levels or neurofibrillary tau tangles in the temporal, mid-frontal, and parietal cortex of PDND and PDD cases [38].…”
Section: Discussionmentioning
confidence: 54%
“…A second recent study in DLB cases showed increased T lymphocyte infiltration in both the grey and white matter of the middle temporal gyrus, in the absence of prominent microglial activation [2]. Similarly, in the substantia nigra of cases with multiple system atrophy compared to controls both CD4 + and CD8 + T lymphocytes were found to be increased [75].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…3) 84 . Of note, neuroinflammation is not a substantive feature of individuals with Lewy pathologies in the absence of AD pathologies 85 . The most common neuropathology in PDD is limbic and/or neocortical Lewy pathology, with few documented cases without this pathology 86 .…”
Section: Neuropathologymentioning
confidence: 98%
“…A demência por corpos de Lewy (DCL) consiste em uma patologia associada a depósitos cerebrais anormais da proteína alfa-sinucleína, os quais formam os corpos de Lewy, sendo considerada na atualidade a segunda causa neurodegenerativa mais comum de demência, somente atrás da Doença de Alzheimer (AMIN et al, 2020;MCKEITH, 2007;MCKEITH et al, 1996).…”
Section: Introductionunclassified